2022
DOI: 10.1021/acsanm.2c03133
|View full text |Cite
|
Sign up to set email alerts
|

Anapole Manipulation in Tailored Si Nanocubes for Near-Field Enhancement and High Q-Factor Resonance

Abstract: Dielectric materials exhibit negligible dissipative losses and strong electromagnetic multipolar optical responses at operating wavelengths compared to metallic materials. In a high-refractive-index dielectric, the destructive interference of the radiation fields from electric and toroidal dipole moments results in the anapole, which has the optical properties of a dark state and cannot emit energy in the far-field region. This study uses periodic Si nanocubes (SN) to support anapole excitation with lattice re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 57 publications
0
7
0
Order By: Relevance
“…To perform a comprehensive analysis of the resonant modes induced in the designed nanostructure, the Cartesian multipole decomposition method is employed to calculate the contributions of various multipole modes to the absorption spectrum [27]. The calculation of various multipole moments, encompassing electric dipole (P), toroidal dipole (T), magnetic dipole (M), electric quadrupole (QE), and magnetic quadrupole (QM) moments, can be achieved by employing the subsequent equations,…”
Section: Modeling and Methodsmentioning
confidence: 99%
“…To perform a comprehensive analysis of the resonant modes induced in the designed nanostructure, the Cartesian multipole decomposition method is employed to calculate the contributions of various multipole modes to the absorption spectrum [27]. The calculation of various multipole moments, encompassing electric dipole (P), toroidal dipole (T), magnetic dipole (M), electric quadrupole (QE), and magnetic quadrupole (QM) moments, can be achieved by employing the subsequent equations,…”
Section: Modeling and Methodsmentioning
confidence: 99%
“…In our earlier simulation study, we showed that stable anapoles can also be formed in simple structures such as high refractive index Tellurium cubes 54 . Tailoring the formation of anapoles is highly useful in the areas of communication and stealth technologies and has been achieved till now by tailoring the geometries 55 , periodicity 56 and active materials 57 . In the current work, we numerically investigate the effect of electrically driven anisotropic LC medium on tailoring the anapole states and their orientations in near and farfield, thus opening up various possibilities in applications of programmable non-radiative modes.…”
Section: Tailoring the Resonant Modes In Liquid Crystal Based All-die...mentioning
confidence: 99%
“…In comparison to metallic metamaterials, high refractive index dielectric nanomaterials exhibit negligible dissipation loss and superior heat resistance, while supporting strong electromagnetic multipole resonances at operating wavelengths [23][24][25][26]. This provides convenience for manipulating the interaction between light and matter.…”
Section: Introductionmentioning
confidence: 99%